O ensino de astronomia em uma vertente investigativa a partir de histórias problematizadoras: o que emerge da fala de professores após experiência em sala de aula - Fernandes, Telma Cristina Dias (2013)
The present work aims at investigating the use of a pedagogical resource entitled Problematizing Narratives (PN). The PNs are short texts which present a hypothetical situation and lead the reader to a problem. From the application of the PNs, seven in total, all about Astronomy related topics, the research presented the following main question: what comprehension emerges from the discourse of a group of teachers who participate of an in-service formation about the use of PNs for the teaching of Astronomy, after its implementation in the classroom? Its aim was to investigate the feasibility of using this pedagogical resource (PN) in the Astronomy Education. The data was obtained from an in-service teachers´ course, held in 2011, with monthly meetings, each of which lasted four hours. The analyzes was carried out considering: the evaluation and use of PN texts; the evaluation and use of material resources with students; the evaluation and comprehension of the student´s role in the implementation of the activities; the evaluation and comprehension of the teacher´s role in the implementation of activities and the evaluation and comprehension of the interference of the conditions of school infrastructure in the implementation of the activities. The results were that the most teachers involved, were favourable to the proposal. They approved of the use of PNs and all its scopes: the methodology, the conception and the materials. However, they approved of it with some considerations, once in many of their testimonies, it was possible to identify many of these teachers referring to limiting factors, such as problems with their personal educational background, as far as the themes were considered, and the necessity of more time than it was offered to them for the preparation and realization of activities. This way, we understand that the adequate use of the material resources which are employed with the PNs can be of vital importance in order to enhance the teaching activities. Therefore, from the stages of this research as well as from the teachers´ testimonies, we could conclude that once the necessary configuration is made, the PNs are feasible and relevant as Astronomy teaching tools.